Magnetic and gravity modeling of a Paleogene diabase plug in Northeast Brazil - Damaceno, Juliana G.; de Castro, David Lopes; Valcácio, Samir N.; Souza, Zorano S. (Journal of applied geophysics, 2017)
A joint magnetic and gravity survey was carried out in a Cenozoic magmatic plug in the northernmost of the Brazilian equatorial margin. The São João plug (0.5km2) is located in the southern border of the Potiguar Basin, belonging to the N–S oriented Macau-Queimadas Alignment formed by Macau magmatism, the youngest magmatism of the Borborema Province. This plug is hosted in Açu and Jandaíra formations, composed of sandstones and limestones that suffered significant thermal changes. The study area is located in a region characterized by a sequence of magnetic highs and lows. Based on the MaxMin technique, no significant remnant magnetization could be detected in the magmatic body. We measured magnetic susceptibility and density of the igneous rocks and their metamorphic and sedimentary bedrocks. The thermal metamorphism promoted an overall increase of bulk density. Joint magnetic and gravity modeling revealed the complex internal geometry of the São João plug, formed by a 400-m deep, probably a lopolith like body with a magmatic conduit as deep as 970m. In addition, 3D modeling allowed mapping other igneous bodies, with no superficial expression, near to the studied plug. •Cenozoic diabase plug investigated in NE Brazil•Detailed magnetic and gravity data were carried out, processed, and interpreted.•2D and 3D modeling are applied to potential field data.•Geophysical model is constrained by measures of magnetic susceptibility and density.•3D geometry of the magmatic body is revealed.